Composite materials, heat spreaders and semiconductor packages

JP7640558B2Active Publication Date: 2025-03-05SUMITOMO ELECTRIC INDUSTRIES LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022541180
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-06
Filing Date
2021-07-13
Publication Date
2025-03-05
Estimated Expiration
2041-07-13

AI Technical Summary

Benefits of technology

【0009】 [本開示の効果] 本開示の複合材料によると、低い線膨張係数及び高い放熱性を両立することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640558000007
    Figure 0007640558000007
  • Figure 0007640558000008
    Figure 0007640558000008
  • Figure 0007640558000009
    Figure 0007640558000009
Patent Text Reader

Abstract

This composite material is provided with a plurality of first layers and a plurality of second layers. The total number of the first layers and the second layers is 5 or more. The first layers and the second layers are alternately stacked in the thickness direction of the composite material in such a manner that the first layers are positioned in a first surface and in a second surface. The first layers are formed of a metal material that is mainly composed of copper. The second layers comprise a molybdenum plate and a copper filler. The molybdenum plate has a first face and a second face, which are end faces in the thickness direction, and a plurality of openings that penetrate through the molybdenum plate from the first face to the second face. The copper filler is arranged within the openings. The thickness of the first layer that is positioned in the first surface is not less than 0.025 mm but not more than 30% of the thickness of the composite material. The thickness of the second layer that is in contact with the first layer positioned in the first surface is not less than 0.05 mm but not more than 35% of the thickness of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a composite material, a heat spreader, and a semiconductor package. This application claims priority to Japanese Patent Application No. 2020-133776, filed on August 6, 2020. The entire contents of the Japanese patent application are incorporated herein by reference. [Background technology]

[0002] Patent Document 1 (JP 2018-18976 A) describes a heat dissipation substrate. The heat dissipation substrate described in Patent Document 1 has a core substrate, a first thermal conductive member, and a second thermal conductive member. The core substrate is made of molybdenum (Mo). The first thermal conductive member and the second thermal conductive member are made of copper (Cu). The core substrate has a first surface and a second surface that is the opposite surface to the first surface. The first thermal conductive member and the second thermal conductive member are disposed on the first surface and the second surface, respectively.

[0003] The core substrate has an opening extending through the core substrate in a direction from the first surface to the second surface, and an insert is disposed within the opening, the insert being made of copper. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2018-18976 A Summary of the Invention

[0005] The composite material of the present disclosure is in the form of a plate and has a first surface and a second surface opposite to the first surface. The composite material includes a plurality of first layers and a plurality of second layers. The sum of the number of the first layers and the number of the second layers is 5 or more. The first layers and the second layers are alternately laminated along the thickness direction of the composite material such that the first layers are located on the first surface and the second surface. The first layer is formed of a metal material mainly composed of copper. The second layer includes a molybdenum plate and a copper filler. The molybdenum plate includes a first surface and a second surface which are end surfaces in the thickness direction, and a plurality of openings penetrating the molybdenum plate from the first surface to the second surface. The copper filler is disposed inside the openings. The thickness of the first layer located on the first surface is 0.025 mm or more and 30 percent or less of the thickness of the composite material. The thickness of the second layer in contact with the first layer located on the first surface is 0.05 mm or more and 35 percent or less of the thickness of the composite material. The number of openings is determined by the area of ​​the first surface. 2 The ratio of the average value of the maximum circle equivalent diameters of the openings to the thickness of the second layer is 0.3 or more and 5.0 or less. [Brief description of the drawings]

[0006] [Figure 1] FIG. 1 is a perspective view of a composite material 10. [Diagram 2] FIG. 2 is a cross-sectional view of a composite material 10. [Diagram 3] FIG. 3 is a plan view of the molybdenum plate 13. As shown in FIG. [Figure 4A] FIG. 4A is a first explanatory diagram of the procedure for producing a sample for measuring the thermal conductivity of the composite material 10 in the thickness direction. [Figure 4B] FIG. 4B is a second explanatory diagram of the procedure for producing a sample for measuring thermal conductivity in the thickness direction of the composite material 10. [Figure 4C] FIG. 4C is a third explanatory diagram of the procedure for producing a sample for measuring thermal conductivity in the thickness direction of the composite material 10. [Diagram 5] FIG. 5 is an explanatory diagram of a method for evaluating the heat dissipation performance of the composite material 10. As shown in FIG. [Figure 6] FIG. 6 is a cross-sectional view of a composite material 10 according to a first modified example. [Figure 7] FIG. 7 is a cross-sectional view of a composite material 10 according to a second modified example. [Figure 8] FIG. 8 is a process diagram showing a method for producing the composite material 10. [Figure 9] FIG. 9 is an exploded perspective view of the semiconductor package 100. As shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] [Problem that this disclosure aims to solve] The heat dissipation substrate described in Patent Document 1 has room for improvement in terms of achieving both a low linear expansion coefficient and high heat dissipation properties.

[0008] The present disclosure has been made in view of the problems of the conventional techniques as described above. More specifically, the present disclosure provides a composite material that can achieve both a low linear expansion coefficient and high heat dissipation properties.

[0009] [Effects of this disclosure] The composite material of the present disclosure can achieve both a low linear expansion coefficient and high heat dissipation properties.

[0010] [Description of the embodiments of the present disclosure] First, embodiments of the present disclosure will be listed and described.

[0011] (1) A composite material according to one embodiment is plate-shaped and has a first surface and a second surface opposite to the first surface. The composite material includes a plurality of first layers and a plurality of second layers. The total number of the first layers and the second layers is 5 or more. The first layers and the second layers are alternately laminated along the thickness direction of the composite material such that the first layers are located on the first surface and the second surface. The first layer is formed of a metal material mainly composed of copper. The second layer includes a molybdenum plate and a copper filler. The molybdenum plate includes a first surface and a second surface which are end surfaces in the thickness direction, and a plurality of openings penetrating the molybdenum plate from the first surface to the second surface. The copper filler is disposed inside the openings. The thickness of the first layer located on the first surface is 0.025 mm or more and 30 percent or less of the thickness of the composite material. The thickness of the second layer in contact with the first layer located on the first surface is 0.05 mm or more and 35 percent or less of the thickness of the composite material. The number of openings is determined by the area of ​​the first surface. 2 The ratio of the average value of the maximum circle equivalent diameters of the openings to the thickness of the second layer is 0.3 or more and 5.0 or less.

[0012] The composite material according to the above item (1) can achieve both a low linear expansion coefficient and high heat dissipation properties.

[0013] (2) In the composite material of (1) above, the ratio of the average value of the maximum circle equivalent diameters of the openings to the thickness of the second layer may be 1.6 or more and less than 5.0.

[0014] (3) In the composite material of (1) or (2) above, the thermal conductivity in the thickness direction may be 290 W / m K or more at room temperature. The linear expansion coefficient in an intralayer direction perpendicular to the thickness direction when the temperature is changed from room temperature to 800°C may be 9.0 ppm / K or less.

[0015] (4) In the composite material of (3) above, the end temperature difference may be 50° C. or less. (5) In the composite material of (1) or (2) above, the thermal conductivity in the thickness direction may be 300 W / m K or more at room temperature. The linear expansion coefficient in an intralayer direction perpendicular to the thickness direction when the temperature is changed from room temperature to 800°C may be 8.5 ppm / K or less.

[0016] (6) In the composite material of (5) above, the end temperature difference may be 40° C. or less. (7) In the composite material of (1) to (6) above, the average circle equivalent diameter of the openings in the first surface and the average circle equivalent diameter of the openings in the second surface may be 0.05 mm or more and 0.35 mm or less.

[0017] (8) In the composite material of (1) to (7) above, the average minimum opening area of ​​the openings may be 57 percent or more and 100 percent or less of the average maximum opening area of ​​the openings.

[0018] (9) In the composite materials of (1) to (8) above, the total number of the first layers and the second layers may be 9 or less.

[0019] (10) A heat spreader according to one embodiment includes the composite material according to any one of (1) to (9) above. A first surface of the composite material is a surface that comes into contact with a heat source.

[0020] (11) A semiconductor package according to one embodiment includes the composite material described above in (1) to (9) and a semiconductor element disposed on a first surface of the composite material.

[0021] (12) The semiconductor package according to (11) above may further include a case member made of a ceramic material. The case member is disposed on the first surface so as to surround the semiconductor element.

[0022] [Details of the embodiment of the present disclosure] Next, details of the embodiments of the present disclosure will be described with reference to the drawings. In the following drawings, the same or corresponding parts are designated by the same reference numerals, and redundant description will not be repeated.

[0023] (Configuration of the composite material according to the embodiment) The configuration of a composite material according to an embodiment (hereinafter referred to as "composite material 10") will be described below.

[0024] Fig. 1 is a perspective view of a composite material 10. As shown in Fig. 1, the composite material 10 has a plate-like shape. The composite material 10 has a first surface 10a and a second surface 10b. The first surface 10a and the second surface 10b are end surfaces in the thickness direction of the composite material 10. In other words, the second surface 10b is the opposite surface to the first surface 10a in the thickness direction of the composite material 10.

[0025] Fig. 2 is a cross-sectional view of a composite material 10. As shown in Fig. 2, the composite material 10 has a plurality of first layers 11 and a plurality of second layers 12. In the example shown in Fig. 2, the number of first layers 11 is four, the number of second layers 12 is three, and the total number of the first layers 11 and the second layers 12 is seven.

[0026] The first layers 11 and the second layers 12 are alternately stacked along the thickness direction of the composite material 10 such that one of the first layers 11 is located on the first surface 10a and the other one of the first layers 11 is located on the second surface 10b. The second layer 12 is sandwiched between the two first layers 11 along the thickness direction of the composite material 10. The thickness of the composite material 10 is defined as thickness T1.

[0027] The first layer 11 is formed of a metal material mainly composed of copper. Here, the term "metal material mainly composed of copper" refers to a metal material having a copper content of 50 mass percent or more. The metal material mainly composed of copper is preferably a copper alloy containing 70 mass percent or more of copper. The first layer 11 is formed of, for example, pure copper. Note that pure copper is a metal material composed of copper and inevitable impurities constituting the remainder.

[0028] Of the first layer 11, the portion located on the first surface 10a is referred to as the first layer 11a. Of the first layer 11, the portion located on the second surface 10b is referred to as the first layer 11b. The thickness of the first layer 11 is referred to as thickness T2. The thickness T2 of the first layer 11a (first layer 11b) is 0.025 mm or more and 30 percent or less of the thickness T1.

[0029] The second layer 12 has a molybdenum plate 13 and a copper filler 14. The molybdenum plate 13 is formed of a metal material mainly composed of molybdenum. The "metal material mainly composed of molybdenum" refers to a metal material having a molybdenum content of 50 mass percent or more. The metal material mainly composed of molybdenum preferably contains 70 mass percent or more of molybdenum. The molybdenum plate 13 is formed of, for example, pure molybdenum. Pure molybdenum is a metal material composed of molybdenum and inevitable impurities constituting the remainder. The copper filler 14 is formed of a metal material mainly composed of copper. The copper filler 14 is formed of, for example, pure copper. The copper filler 14 is preferably formed of the same material as the first layer 11.

[0030] The molybdenum plate 13 is a plate-shaped body. The molybdenum plate 13 has a first surface 13a and a second surface 13b. The first surface 13a and the second surface 13b are end surfaces in the thickness direction of the composite material 10. In other words, the second surface 13b is the surface opposite to the first surface 13a in the thickness direction of the composite material 10.

[0031] The molybdenum plate 13 has a plurality of openings 13c. The openings 13c penetrate the molybdenum plate 13 in the direction from the first surface 13a to the second surface 13b. 2 The number of openings 13c per unit area (the total number of openings 13c divided by the area of ​​the first surface 10a (second surface 10b)) is equal to or greater than 2 and equal to or less than 12. The copper filler 14 is disposed inside the openings 13c.

[0032] Of the second layer 12, the part in contact with the first layer 11a is referred to as the second layer 12a. Of the second layer 12, the part in contact with the first layer 11b is referred to as the second layer 12b. The thickness of the second layer 12 is referred to as thickness T3. The thickness T3 of the second layer 12a (second layer 12b) is 0.05 mm or more and 35 percent or less of the thickness T1.

[0033] 3 is a plan view of the molybdenum plate 13. As shown in FIG. 3, the opening 13c has a circular shape in a plan view. However, the shape of the opening 13c in a plan view is not limited to a circular shape. The opening 13c may have, for example, an elliptical shape, a polygonal shape, or any other shape in a plan view. The circle-equivalent diameter of the opening 13c in a plan view is defined as the opening diameter D. The opening diameter D is obtained by calculating the square root of the area of ​​the opening 13c in a plan view divided by π / 4.

[0034] The opening diameter D is constant between the first surface 13a and the second surface 13b. It is okay The opening diameter D may vary between the first surface 13a and the second surface 13b, and may not be constant between the first surface 13a and the second surface 13b. When the opening diameter D varies between the first surface 13a and the second surface 13b, the opening diameter D may decrease from one of the first surface 13a and the second surface 13b toward the other of the first surface 13a and the second surface 13b. For a certain opening, the maximum value of the opening diameter D in the thickness direction is defined as the opening diameter D. max Let us assume that.

[0035] Opening diameter D max The average value of (opening diameter D max The average equivalent circular diameter is defined as the sum of the diameters of all openings 13c and the sum divided by the total number of openings 13c. For one second layer 12, the value obtained by dividing the average equivalent circular diameter by the thickness T3, i.e., the ratio of the average equivalent circular diameter to the thickness T3, is 0.3 or more and 5.0 or less. The ratio of the average equivalent circular diameter to the thickness T3 is preferably 1.6 or more and less than 5.0.

[0036] It is preferable that the average value of the opening diameter D on the first surface 13a (the value obtained by summing the opening diameter D on the first surface 13a for all openings 13c and dividing this sum by the total number of openings 13c) and the average value of the opening diameter D on the second surface 13b (the value obtained by summing the opening diameter D on the second surface 13b for all openings 13c and dividing this sum by the total number of openings 13c) are each 0.05 mm or more and 0.35 mm or less.

[0037] The opening area of ​​the opening 13c is measured on a plane parallel to the first surface 13a. The minimum value of the opening area of ​​the opening 13c when measured between the first surface 13a and the second surface 13b along the thickness direction of the molybdenum plate 13 is the minimum opening area of ​​the opening 13c. The maximum value of the opening area of ​​the opening 13c when measured between the first surface 13a and the second surface 13b along the thickness direction of the molybdenum plate 13 is the maximum opening area of ​​the opening 13c. It is more preferable that the average value of the minimum opening area of ​​the opening 13c (the value obtained by summing up the minimum opening areas of the openings 13c for all the openings 13c and dividing the sum by the total number of the openings 13c) is 57 percent or more and 100 percent or less of the average value of the maximum opening area of ​​the opening 13c (the value obtained by summing up the maximum opening areas of the openings 13c for all the openings 13c and dividing the sum by the total number of the openings 13c).

[0038] The thermal conductivity of the composite material 10 in the thickness direction is preferably 290 W / m K or more at room temperature. The thermal conductivity of the composite material 10 in the thickness direction is preferably 300 W / m K or more at room temperature. Here, "room temperature" refers to 27°C.

[0039] The thermal conductivity of the composite material 10 in the thickness direction is measured using a laser flash method. In the laser flash method, the thermal diffusion coefficient of the composite material 10 is measured using an LFA457MicroFlash (manufactured by NETZSCH), and the thermal conductivity of the composite material 10 in the thickness direction is calculated based on the thermal diffusion coefficient and the volume ratio and specific heat of each of the constituent materials of the composite material 10. In calculating the thermal conductivity, the specific heat of each of the constituent materials is determined based on "Metal Data Book, 4th Edition" (2004, Maruzen Publishing), edited by the Japan Institute of Metals. Prior to measuring the thermal conductivity of the composite material 10, the thermal conductivity of a pure copper sample of the same shape is measured under the same conditions, and the measurement result is corrected using the result as a reference.

[0040] Fig. 4A is a first explanatory diagram of the procedure for preparing a sample for measuring thermal conductivity in the thickness direction of a composite material 10. As shown in Fig. 4A, a flake 15 is cut out from the composite material 10 to be measured. The thickness, length and width of the flake 15 are t (mm), B (mm) and C (mm), respectively.

[0041] Let X be the number obtained by rounding up the decimal point of 2 divided by t. Let Y1 be the number obtained by rounding up the decimal point of 10 divided by B. Let Y2 be the number obtained by rounding up the decimal point of 10 divided by C. A number of slices 15 equal to the product of X, Y1, and Y2 are cut out from the composite material 10 to be measured.

[0042] FIG. 4B is a second explanatory diagram of the procedure for preparing a sample for measuring the thermal conductivity in the thickness direction of the composite material 10. As shown in FIG. 4B, a block 16 is prepared from X pieces of flakes 15. The thickness, length and width of the block 16 are approximately 2 (mm), B (mm) and C (mm), respectively. In preparing the block 16, first, X pieces of flakes 15 are stacked. At this time, an irregular powder made of pure silver with an average particle size of 4 μm is placed between adjacent flakes 15. The amount of the irregular powder placed between adjacent flakes 15 is 100 mm. 2 The average molecular weight is 0.2g ±30 percent.

[0043] In the production of the block 16, secondly, a rectangular mold (not shown) having an opening with inner dimensions B (mm) x C (mm) is prepared, and the stacked flakes 15 are placed in the opening. The mold is made of graphite. In the production of the block 16, thirdly, the stacked flakes 15 are heat-treated with a load P applied. The load P is 4.9 N or more and 9.8 N or less. The heat treatment is performed in an inert gas atmosphere. The heat treatment is performed at a holding temperature of 900°C and for a holding time of 10 minutes. The heat treatment softens and deforms the amorphous powder, bonding adjacent flakes 15 together, thereby producing the block 16.

[0044] FIG. 4C is a third explanatory diagram of the procedure for preparing a measurement sample for the thermal conductivity in the thickness direction of the composite material 10. As shown in FIG. 4C, a measurement sample 17 having a height of about 10 mm, a width of about 10 mm, and a thickness of about 2 mm is prepared by arranging Y1 blocks 16 vertically and Y2 blocks 16 horizontally. When arranging Y1 blocks 16 vertically and Y2 blocks horizontally, adjacent blocks 16 are bonded to each other with an adhesive member. The adhesive member used may be a silver brazing foil, a ceramic adhesive, or the like, capable of withstanding temperatures up to about 800°C. The blocks 16 arranged vertically and horizontally in Y1 and Y2 rows may be fixed by winding a stainless steel wire or the like around the outer periphery.

[0045] The linear expansion coefficient of the composite material 10 in the in-layer direction (the direction perpendicular to the thickness direction) when the temperature changes from room temperature to 800° C. is preferably 9.0 ppm / K or less. The linear expansion coefficient of the composite material 10 in the in-layer direction when the temperature changes from room temperature to 800° C. is more preferably 8.5 ppm / K or less.

[0046] The linear expansion coefficient in the in-layer direction of the composite material 10 when the temperature changes from room temperature to 800°C is calculated by measuring the expansion displacement in the in-layer direction of the composite material 10 in the temperature range from room temperature to 800°C using a TDS5000SA (manufactured by Bruker AXS). When calculating the linear expansion coefficient in the in-layer direction of the composite material 10 when the temperature changes from room temperature to 800°C, the planar shape of the composite material 10 is a rectangle of 3 mm x 15 mm. The measured value is the average value for three samples.

[0047] The end temperature difference of the composite material 10 is preferably 50°C or less. The end temperature difference of the composite material 10 is more preferably 40°C or less. FIG. 5 is an explanatory diagram of a method for evaluating the heat dissipation performance of the composite material 10. FIG. 5 shows a schematic view of one side of the composite material 10. The composite material 10 is cut into a rectangular shape having a length and width of 10 mm when viewed from a direction perpendicular to the first surface 10a. A heating element 70 is brought into contact with the center of the first surface 10a of the cut composite material 10. The heating element 70 has a rectangular shape having a length and width of 10 mm when viewed from a direction perpendicular to the first surface 10a. The heating value of the heating element 70 is 50W.

[0048] The aluminum fin 80 is bonded to the second surface 10b of the cut composite material 10 using silicone oil (G-751 manufactured by Shin-Etsu Chemical Co., Ltd.) by applying a load of 9.8 N with the silicone oil placed between the second surface 10b of the cut composite material 10 and the aluminum fin 80.

[0049] The temperature at the interface between the first surface 10a of the cut composite material 10 and the heating element 70 is defined as a first temperature. The temperature at the end (corner) of the first surface 10a of the cut composite material 10 is defined as a second temperature. The temperature at the interface between the second surface 10b of the cut composite material 10 and the aluminum fin 80 is defined as a third temperature. The first temperature, the second temperature, and the third temperature are measured by a thermocouple (not shown). Air cooling of the aluminum fin 80 is controlled so that the third temperature is 25°C±3°C. The ambient temperature as the measurement environment is 25°C±5°C.

[0050] The difference between the first temperature and the second temperature (first temperature - second temperature) when 30 seconds or more have elapsed since the heating element 70 was brought into contact with the first surface 10a of the cut composite material 10 and the temperature has become steady is the end temperature difference of the composite material 10. This end temperature difference is measured 10 times, and the average value is adopted. In other words, the end temperature difference of the composite material 10 is the difference between the temperature at the part of the first surface 10a where the heating element 70 is in contact and the temperature at the end (corner) of the first surface 10a in a state where the heating element 70 is in contact with the first surface 10a and the aluminum fin 80 is bonded to the second surface 10b. The smaller the end temperature difference, the better the thermal conduction in the in-layer direction of the composite material 10.

[0051] <Modification> Fig. 6 is a cross-sectional view of a composite material 10 according to a first modified example. Fig. 7 is a cross-sectional view of a composite material 10 according to a second modified example. As shown in Fig. 6, the total number of first layers 11 and the number of second layers 12 may be 5. As shown in Fig. 7, the total number of first layers 11 and the number of second layers 12 may be 9.

[0052] (Method of manufacturing a composite material according to an embodiment) A method for producing the composite material 10 will now be described.

[0053] Fig. 8 is a process diagram showing a method for producing the composite material 10. As shown in Fig. 8, the method for producing the composite material 10 includes a preparation step S1, a hole making step S2, and a joining step S3.

[0054] In the preparation step S1, a first plate material and a second plate material are prepared. The first plate material is made of a metal material mainly composed of copper. The second plate material is made of a metal material mainly composed of molybdenum.

[0055] In the hole making process S2, holes are made in the second plate. By the hole making process, a plurality of openings penetrating the second plate in the thickness direction are formed in the second plate. As a result, the second plate becomes a molybdenum plate 13. The hole making process in the second plate is performed by, for example, etching or laser irradiation.

[0056] In the joining step S3, first, the first plate material and the molybdenum plate 13 are alternately stacked in a mold (hereinafter, the first plate material and the molybdenum plate 13 alternately stacked are referred to as a laminate). The mold is made of, for example, graphite. The first plate material and the molybdenum plate 13 are stacked so that the first plate material is located on the surface of the laminate.

[0057] Secondly, in the joining step S3, the laminate is heated and pressurized. The heating temperature is set to a temperature that is lower than the melting point of the first plate material and at which the first plate material is sufficiently softened. The heating temperature is, for example, 1000°C. Pressurization is performed along the thickness direction of the laminate. Pressurization is performed at a pressure necessary to flow the first plate material softened by heating. Pressurization is performed at a pressure of, for example, 50 MPa.

[0058] The above-mentioned heating and pressurization causes the first plate material to flow, and as a result, the first plate material fills the openings 13c of the molybdenum plate 13 and becomes the copper filler 14. The remaining part of the first plate material that is not filled in the openings 13c becomes the first layer 11.

[0059] (Configuration of Semiconductor Package According to the Embodiment) The configuration of a semiconductor package according to an embodiment (hereinafter referred to as a "semiconductor package 100") will be described below.

[0060] Fig. 9 is an exploded perspective view of the semiconductor package 100. As shown in Fig. 9, the semiconductor package 100 includes a composite material 10, a semiconductor element 20, a case member 30, a lid 40, and terminals 50a and 50b.

[0061] The composite material 10 functions as a heat spreader in the semiconductor package 100. The semiconductor element 20 is disposed on the first surface 10a. A heat transfer member may be interposed between the semiconductor element 20 and the first surface 10a. The semiconductor element 20 becomes a heat source during operation.

[0062] The case member 30 is formed of, for example, a ceramic material. The ceramic material is, for example, alumina (Al2O3). The case member 30 is disposed on the first surface 10a so as to surround the semiconductor element 20. The lower end (the end on the first surface 10a side) of the case member 30 is joined to the first surface 10a by, for example, brazing. The lid 40 is formed of, for example, a ceramic material or a metal material. The lid 40 closes the upper end side of the case member 30.

[0063] The terminals 50a and 50b are inserted into the case member 30. As a result, one ends of the terminals 50a and 50b are located within the space defined by the first surface 10a, the case member 30, and the cover 40, and the other ends of the terminals 50a and 50b are located outside the space. b is made of, for example, a metal material, such as kovar.

[0064] Although not shown, one ends of the terminals 50a and 50b are electrically connected to the semiconductor element 20. The other ends of the terminals 50a and 50b of the semiconductor package 100 are electrically connected to a device or circuit other than the semiconductor package 100.

[0065] A heat dissipation member 60 is attached to the second surface 10b. The heat dissipation member 60 is, for example, a metal plate in which a flow path through which a refrigerant flows is formed. However, the heat dissipation member 60 is not limited to this. The heat dissipation member 60 may be, for example, a cooling fin. A heat transfer member may be interposed between the heat dissipation member 60 and the second surface 10b.

[0066] (Effects of the composite material according to the embodiment) The effects of the composite material 10 will be described below.

[0067] In order to efficiently dissipate heat from the heat source from the first surface 10a (second surface 10b), it is effective to increase the thermal conductivity on the first surface 10a (second surface 10b) side to diffuse the heat from the heat source along the in-layer direction.

[0068] In the composite material 10, the thickness T2 of the first layer 11a (first layer 11b) having a relatively high thermal conductivity is ensured to be 0.025 mm or more. Therefore, the composite material 10 can efficiently dissipate heat from the heat source from the first surface 10a (second surface 10b).

[0069] The composite material 10 is exposed to high temperatures (for example, about 800° C.) when the case member 30 is brazed, for example. Therefore, the composite material 10 is required to have small thermal expansion when exposed to high temperatures. In the composite material 10, the thickness T3 of the second layer 12a (second layer 12b) having a relatively low linear expansion coefficient is ensured to be 0.05 mm or more. In addition, in the composite material 10, the thickness T2 of the first layer 11a (first layer 11b) is set to 30 percent or less of the thickness T1, so that the first layer 11a (first layer 11b) having a relatively high linear expansion coefficient does not become excessively thick. Therefore, the composite material 10 suppresses thermal expansion when exposed to high temperatures.

[0070] To improve the heat dissipation of the composite material 10, it is necessary to increase not only the thermal conductivity on the first surface 10a (second surface 10b) side but also the thermal conductivity of the entire composite material 10. However, if the ratio of molybdenum in the composite material 10 is increased, the linear expansion coefficient of the entire composite material 10 decreases, while the thermal conductivity of the entire composite material 10 decreases.

[0071] Area of ​​the first surface 10a (second surface 10b) 1 mm 2As the number of openings 13c per unit area increases or the value obtained by dividing the average equivalent circle diameter of openings 13c by thickness T3 increases, the ratio of molybdenum in composite material 10 decreases, and the thermal conductivity of the entire composite material 10 decreases. In addition, as the thickness T3 of second layer 12a (second layer 12b) increases, the ratio of molybdenum in composite material 10 increases, and the thermal conductivity of the entire composite material 10 decreases.

[0072] In the composite material 10, the number of openings 13c is 1 mm2 of the area of ​​the first surface 10a (second surface 10b). 2 The thickness T3 of the second layer 12a (12b) is set to 35 percent or less of the thickness T1, so that the thickness T3 of the second layer 12a (12b) is not excessively thick. Therefore, the composite material 10 maintains a balance between the thermal conductivity and the linear expansion coefficient of the composite material 10 as a whole.

[0073] As described above, the composite material 10 can achieve both a low linear expansion coefficient and high heat dissipation properties.

[0074] (Experimental Example) Samples 1 to 48 were prepared to confirm the effect of the composite material 10. In Samples 1 to 48, the first layer 11 was made of pure copper. In Samples 1 to 48, the molybdenum plate 13 was made of pure molybdenum, and the copper filler 14 was made of pure copper.

[0075] Tables 1, 2, and 3 show the dimensions of the composite material 10 in Samples 1 to 48. The thickness T2 of the layers other than the first layer 11a and the first layer 11b is determined from the thickness T1 of the composite material 10, the thickness T2 of the first layer 11a and the first layer 11b, and the thickness T3 of the second layer 12, and is therefore omitted in Tables 1 to 3. In Samples 27 to 48, the thickness T3 of the second layer 12a and the second layer 12b is equal to the thickness T3 of the second layer 12 other than the second layer 12a and the second layer 12b.

[0076] Condition A is that the thickness T1 of the first layer 11a (first layer 11b) is 0.025 mm or more and 30 percent or less of the thickness T3. Condition B is that the thickness T2 of the second layer 12a (second layer 12b) is 0.05 mm or more and 30 percent or less of the thickness T3.

[0077] Area of ​​the first surface 10a (second surface 10b) 1 mm 2 Condition C is that the number of openings 13c per unit area is 2 or more and 12 or less. Condition D is that the value obtained by dividing the average equivalent circular diameter of openings 13c by thickness T3 is 0.3 or more and 5.0 or less. Condition E is that the value obtained by dividing the average equivalent circular diameter of openings 13c by thickness T3 is 1.6 or more and less than 5.0.

[0078] In Sample 1 to Sample 3, Sample 8, Sample 12, Sample 15, Sample 27, Sample 32, Sample 39, and Sample 43, at least one of Conditions A to D was not satisfied. In the other samples, all of Conditions A to D were satisfied.

[0079] In Samples 4 to 7, Sample 13, Sample 14, Sample 18 to Sample 22, Sample 28 to Sample 31, Sample 34, Sample 36 to Sample 38, Sample 40 to Sample 42, and Sample 44 to Sample 48, Condition E was further satisfied.

[0080] [Table 1]

[0081] [Table 2]

[0082] [Table 3]

[0083] For Samples 1 to 48, the thermal conductivity in the thickness direction, the linear expansion coefficient in the layer direction when the temperature was changed from room temperature to 800° C., and the end temperature difference were measured.

[0084] Tables 4, 5 and 6 show the results of measurements of thermal conductivity in the thickness direction, linear expansion coefficient in the layer direction when the temperature was changed from room temperature to 800° C., and end temperature difference for Samples 1 to 48.

[0085] [Table 4]

[0086] [Table 5]

[0087] [Table 6]

[0088] Condition F is that the thermal conductivity in the thickness direction is 290 W / m K or more. Condition G is that the linear expansion coefficient in the layer direction when the temperature changes from room temperature to 800°C is 9.0 ppm / K or less. Condition H is that the end temperature difference is 50°C or less.

[0089] In Samples 1 to 3, Sample 8, Sample 12, Sample 15, Sample 27, Sample 32, Sample 39, and Sample 43, at least one of Conditions F to H was not satisfied. On the other hand, in the other samples, all of Conditions F to H were satisfied. From this comparison, it was experimentally shown that by satisfying all of Conditions A to D, the composite material 10 has both a low linear expansion coefficient and high heat dissipation properties.

[0090] Condition I is that the thermal conductivity in the thickness direction is 300 W / m K or more. Condition J is that the linear expansion coefficient in the layer direction when the temperature changes from room temperature to 800°C is 8.5 ppm / K or less. Condition K is that the end temperature difference is 40°C or less.

[0091] Conditions I to K were further satisfied in Samples 4 to 7, Sample 13, Sample 14, Sample 18 to Sample 22, Sample 28 to Sample 31, Sample 34, Sample 36 to Sample 38, Sample 40 to Sample 42, and Sample 44 to Sample 48. From this comparison, it was experimentally shown that by further satisfying Condition E, the low linear expansion coefficient and high heat dissipation property of the composite material 10 can be achieved at an even higher level.

[0092] The embodiments disclosed herein are illustrative in all respects and should not be considered as limiting. The scope of the present invention is defined by the claims, not by the above-described embodiments, and is intended to include all modifications within the scope and meaning equivalent to the claims. [Explanation of symbols]

[0093] 10 composite material, 10a first surface, 10b second surface, 11, 11a, 11b first layer, 12, 12a, 12b second layer, 13 molybdenum plate, 13a first surface, 13b second surface, 13c opening, 14 copper filler, 15 thin piece, 16 block, 17 measurement sample, 20 semiconductor element, 30 case member, 40 lid, 50a, 50b terminal, 60 heat dissipation member, 70 heating element, 80 aluminum fin, 100 semiconductor package, D opening diameter, S1 preparation process, S2 Drilling holes process, S3 joining process, T1, T2, T3 thickness.

Claims

1. A plate-shaped composite material having a first surface and a second surface opposite to the first surface, A plurality of first layers and a plurality of second layers, the sum of the number of the first layers and the number of the second layers is 5 or more; the first layer and the second layer are alternately laminated along a thickness direction of the composite material, the layer constituting the first surface and the second surface is the first layer, The first layer is formed of a metal material containing copper as a main component, the second layer includes a molybdenum plate and a copper filler; the molybdenum plate has a plurality of openings penetrating the molybdenum plate in the thickness direction; The copper filler is disposed so as to fill the inside of the opening, the first layer constituting the first surface has a thickness of 0.025 mm or more and 30 percent or less of the thickness of the composite material; the second layer in contact with the first layer constituting the first surface has a thickness of 0.05 mm or more and 35% or less of a thickness of the composite material; In any one of the second layers, The number of the openings is determined based on the area of ​​the first surface. 2 2 to 12, A composite material, wherein a value obtained by dividing an average equivalent circular diameter of the openings by a thickness of the second layer is 0.3 or more and 5.0 or less.

2. The composite material according to claim 1 , wherein a value obtained by dividing an average equivalent circular diameter of the openings by a thickness of the second layer is 1.6 or more and less than 5.

0.

3. The thermal conductivity in the thickness direction is 290 W / m K or more at room temperature, 3. The composite material according to claim 1, wherein the linear expansion coefficient in an intralayer direction perpendicular to the thickness direction when the temperature is changed from room temperature to 800° C. is 9.0 ppm / K or less.

4. 4. The composite material of claim 3, wherein the end temperature differential is 50° C. or less.

5. The thermal conductivity in the thickness direction is 300 W / m K or more at room temperature, 3. The composite material according to claim 1, wherein the linear expansion coefficient in an intralayer direction perpendicular to the thickness direction when the temperature is changed from room temperature to 800° C. is 8.5 ppm / K or less.

6. 6. The composite material of claim 5, wherein the end temperature difference is 40°C or less.

7. The molybdenum plate has a first surface and a second surface which are end surfaces in the thickness direction, 7. The composite material according to claim 1, wherein an average value of the equivalent circle diameter of the openings in the first surface and an average value of the equivalent circle diameter of the openings in the second surface are 0.05 mm or more and 0.35 mm or less.

8. 8. The composite material according to claim 1, wherein the average minimum opening area of ​​the openings is greater than or equal to 57 percent and less than or equal to 100 percent of the average maximum opening area of ​​the openings.

9. 9. The composite material according to claim 1 , wherein the sum of the number of the first layers and the number of the second layers is 9 or less.

10. The composite material according to any one of claims 1 to 9, The first surface is a contact surface with a heat source.

11. The composite material according to any one of claims 1 to 9; a semiconductor element disposed on the first surface.

12. Further comprising a case member formed of a ceramic material; The semiconductor package according to claim 11 , wherein the case member is disposed on the first surface so as to surround the semiconductor element.

13. A plate-shaped composite material having a first surface and a second surface opposite to the first surface, A plurality of first layers and a plurality of second layers, the sum of the number of the first layers and the number of the second layers is 5 or more and 9 or less, the first layer and the second layer are alternately laminated along a thickness direction of the composite material, the layer constituting the first surface and the second surface is the first layer, The first layer is formed of a metal material containing copper as a main component, the second layer includes a molybdenum plate and a copper filler; the molybdenum plate has a plurality of openings penetrating the molybdenum plate in the thickness direction; The copper filler is disposed so as to fill the inside of the opening, the first layer constituting the first surface has a thickness of 0.025 mm or more and 30 percent or less of the thickness of the composite material; the second layer in contact with the first layer constituting the first surface has a thickness of 0.05 mm or more and 35% or less of a thickness of the composite material; In any one of the second layers, The number of the openings is determined based on the area of ​​the first surface. 2 2 to 12, a value obtained by dividing an average equivalent circular diameter of the openings by a thickness of the second layer is 0.3 or more and 5.0 or less; The thermal conductivity in the thickness direction is 290 W / m K or more at room temperature, The linear expansion coefficient in the in-layer direction perpendicular to the thickness direction when the temperature is changed from room temperature to 800° C. is 9.0 ppm / K or less, The molybdenum plate has a first surface and a second surface which are end surfaces in the thickness direction, an average value of the equivalent circle diameter of the openings in the first surface and an average value of the equivalent circle diameter of the openings in the second surface are 0.05 mm or more and 0.35 mm or less; The composite material, wherein the average minimum open area of ​​the openings is greater than or equal to 57 percent and less than or equal to 100 percent of the average maximum open area of ​​the openings.

Citation Information

Patent Citations

  • Heat dissipation substrate, semiconductor package, semiconductor module, and method for manufacturing heat dissipation substrate

    JP2018018976A

  • Heat dissipating substrate, heat dissipating substrate electrode, semiconductor package, and semiconductor module

    JP2018182088A

  • Heat dissipation substrate and electronic device

    WO2019208577A1